2021
DOI: 10.1155/2021/2231759
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Indigenous Knowledge into Adult Learning Material Development and the Facilitation Methodology

Abstract: Connecting indigenous knowledge systems and practices with adult education programs has priceless value of promoting and transferring indigenous perspectives from generation to generation. Indeed, education is the surest path to ensuring social continuity when it ought to be based on the real-life experiences of learners and what their immediate environment and social realities entail. This demands the development of relevant adult learning materials and the utilization of participatory facilitation methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Unfortunately, major challenges facing the inclusion of IK into AE learning materials and facilitation methodology and contextual consideration were not explored adequately and he suggested to explore. In this sense, this study is the extension of work of Assefa's [27] study. Inspired by this, therefore, the researchers initiated to study indigenous based AE learning materials development with special emphasis to exploring hindering factors and forwarding some contextual considerations.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Unfortunately, major challenges facing the inclusion of IK into AE learning materials and facilitation methodology and contextual consideration were not explored adequately and he suggested to explore. In this sense, this study is the extension of work of Assefa's [27] study. Inspired by this, therefore, the researchers initiated to study indigenous based AE learning materials development with special emphasis to exploring hindering factors and forwarding some contextual considerations.…”
Section: Introductionmentioning
confidence: 88%
“…In doing this study, qualitative research approach with case study design recognized by [48] was employed. Since this study is the extension work of Assefa [27] entitled Integration of Indigenous Knowledge into Adult Learning Material Development and the Facilitation Methodology, he suggested that "the integration of IK into AE practice has been practiced fully of many ups and downs. Therefore, researchers are suggested to scrutinize practical challenges, available opportunities, and contextual considerations of IK and AE" (pp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of their learning need is to connect learning to this knowledge/experience base. Adult learners should draw out participants’ experiences and knowledge relevant to the topic (Assefa, 2021 ; Peregoy et al, 2023 ). The MLGP’s impact extends beyond personal transformation to encompass leadership competence and health system improvements.…”
Section: Discussionmentioning
confidence: 99%